Chodź, pomaluj mój świat – na żółto i na niebiesko - Kruczek, Daria; Lis, Katarzyna (Wydawnictwo Politechniki Łódzkiej, 2021)
Celem referatu jest zbadanie i porównanie różnic w postrzeganiu postmodernistycznej architektury osiedli mieszkalnych i współczesnych starówek. Analiza skupiona jest na dwóch aspektach– zjawisku retrowersji oraz charakterystycznej kolorystyce elewacji dominującej w budownictwie z wielkiej płyty.

The main purpose of this paper is to investigate and compare the differences in perceiving postmodernist architecture of residential blocks of flats with contemporary old towns in some Polish cities. The conducted analysis focuses on two characteristics of postmodernism – retroversion method and distinctive facade colouring of the buildings made in large prefabricated panel technology.
Come, colour my world
Keywords: postmodernizm; postrzeganie architektury; historia architektury; postmodernism; perception of architecture; history of architecture